The cult of Saint Christopher in the diocese of Rab - Potočnjak, Saša,Španjol-Pandelo, Barbara (Ikon;Rijeka, 2021;Band 14 (2021), Seite 221-232, 2021)
The cult of Saint Christopher represents an important matter in defining the construction of self-identity of the community of Rab as one of the Eastern Adriatic medieval communitas, which local cultural imagination has been modelling for centuries. From the thirteenth and especially during the fourteenth and the fifteenth centuries the community of Rab was constructing its identity based on the local narrative about victorious miracles performed by the relic of St Christopher’s skull. The importance of his presence as a local patron is examined and discussed with regard to the saint’s relic, visual representations and late medieval written sources with special attention to the Historias miraculorum sancti Christophori tres victorias descriptas, edited by bishop Juraj Hermolais (Georgius de Hermolais) in 1308.
Keywords: Christophorus; Georgius; Heiligenverehrung; Heiligenvita; Heiligenbild